2007
DOI: 10.1074/jbc.m608456200
|View full text |Cite
|
Sign up to set email alerts
|

JunB and JunD Regulate Human Heme Oxygenase-1 Gene Expression in Renal Epithelial Cells

Abstract: Heme oxygenase-1 is a highly inducible gene, the product of which catalyzes breakdown of the prooxidant heme. The purpose of this study was to investigate the regulation of the human heme oxygenase-1 gene in renal epithelial cells. DNase I hypersensitivity studies identified three distal sites (HS-2, -3, and -4) corresponding to approximately ؊4.0, ؊7.2, and ؊9.2 kb, respectively, of the heme oxygenase-1 promoter in addition to one proximal region, HS-1, which we have shown previously to be an E box. In vivo d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
49
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 60 publications
(60 reference statements)
6
49
0
Order By: Relevance
“…These results show that JunD and JunB have opposing roles in regulating ethanol-mediated HO-1 transcription. Previous studies in HK-2 cells, an immortalized human renal epithelial cell line, show that hemin-induced HO-1 promoter activity is augmented by c-Jun and JunB but repressed by JunD (27). These results and data from our studies implicate differential roles of JunD and JunB in regulating HO-1 gene expression and are context-sensitive to the nature of stimuli and cell type.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…These results show that JunD and JunB have opposing roles in regulating ethanol-mediated HO-1 transcription. Previous studies in HK-2 cells, an immortalized human renal epithelial cell line, show that hemin-induced HO-1 promoter activity is augmented by c-Jun and JunB but repressed by JunD (27). These results and data from our studies implicate differential roles of JunD and JunB in regulating HO-1 gene expression and are context-sensitive to the nature of stimuli and cell type.…”
Section: Discussionsupporting
confidence: 81%
“…The targets of the inhibitors and siRNA mentioned are described in supplemental Table I. The human Ϫ9.2-kb HO-1-pGL3, Ϫ4.5-kb HO-1-pGL3, and mutant construct of the Ϫ4.5-kb HO-1-pGL3 promoter with a deletion of the ARE enhancer region E1 and the JunB expression plasmid were generously provided by Dr. Anupam Agarwal (University of Alabama, Birmingham, AL) (27,36). Mutant constructs of the HO-1-luc promoter were generated using wild-type Ϫ4.5-kb HO-1 construct as a template with the QuikChange site-directed mutagenesis kit (Stratagene, Cedar Creek, TX) using the primers shown in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, studies have shown that there are at least five putative HRE-1 to -5 in the human PAI-1 promoter and that HIF-1␣ interacts only with HRE-2 to regulate PAI-1 transcription in response to hypoxia (17). Our study shows that PlGF induces activity of the human PAI-1 promoter via HRE-1 and -2 (but not HRE-3, -4, or -5 (48). In contrast, we show that PlGF-mediated PAI-1 transcription is activated by JunD, and overexpression of JunB has no effect.…”
Section: Discussionmentioning
confidence: 52%
“…Jun proteins can form AP-1 homodimers or heterodimers among themselves or with members of the related Fos or ATF (activating transcription factor) protein families and regulate the transcription of target genes by binding to specific promoter DNA elements such as TGAGTCA and TGACGTCA (17,41,58,59). All three Jun proteins (c-Jun, JunB, and JunD) are similar in DNA-binding affinity, but their patterns of expression vary in response to stress and during cell proliferation and transformation (6,10,17,48,56,59). Although c-Jun and JunB behave as immediate-early response genes and enhance the G 1 -to-S-phase transition upon mitogenic stimulation, the overexpression of JunD inhibits cell proliferation (14,29,38).…”
mentioning
confidence: 99%